EVALUATION OF THE EFFICACY OF ELECTROACUPUNCTURE IN THE TREATMENT OF OCULOMOTOR NERVE (CRANIAL NERVE III) PALSY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic efficacy and safety of electroacupuncture in patients with post-traumatic oculomotor nerve (cranial nerve III) palsy after etiological treatment. Methods: A before–after clinical intervention study was conducted on 30 patients with post-traumatic oculomotor nerve palsy. Outcome measures included clinical symptoms, the MRD1 index for ptosis assessment, levator palpebrae superioris muscle function, Traditional Medicine manifestations, and adverse events at baseline (D0) and after 20 days of treatment (D20).Results: After treatment, mean palpebral fissure width increased from 0.93 ± 1.53 mm to 7.60 ± 2.22 mm; levator muscle function score decreased from 3.93 ± 0.25 to 1.30 ± 0.47; and ptosis score decreased from 2.90 ± 0.31 to 0.83 ± 0.75 (p
Keywords: Oculomotor nerve palsy; electroacupuncture; ptosis; ocular motor function.